Identification of piRNAs in the testes of Sunite and Small-tailed Han sheep. Issue 1 (1st February 2021) - He, Xiaolong; Li, Bei; Fu, Shaoyin; Wang, Biao; Qi, Yunxia; Da, Lai; Te, Rigele; Sun, Suzhen; Liu, Yongbin; Zhang, Wenguang
Abstract: P-element-induced wimpy testis-interacting RNAs (piRNAs) are small RNAs that are essential for mammalian spermatogenesis and testicular development. Comparative analyses of the molecular mechanisms of spermatogenesis among different organisms are therefore dependent on accurate piRNA characterizations. In this study, we identified piRNAs in the testes of two breeds of Mongolian sheep: the Sunite (SN), which has a low reproductive rate, and Small-tailed Han (STH), which has a high reproductive rate. A thorough understanding of the mechanisms underlying the differences in fecundity between the two breeds might provide insights for the improvement of fertility and reproductive success in these and other sheep breeds. We identified 835 piRNAs and 206 piRNA clusters across the two breeds. Of these, 29 putative piRNAs were expressed in the SN samples only, and 229 putative piRNAs were expressed in the STH samples only. In addition, 206 piRNA clusters were upregulated in STH sheep as compared to the SN sheep. Functional pathway analysis indicated that the genes neighboring the predicted piRNAs were likely associated with spermatogenesis. piRNAs might thus be linked to male fecundity in sheep. Our results increase knowledge of the association between piRNAs and male fertility.